Voltage sag mitigation using flywheel inverter system - Bashi, Sinan Mahmod; Mariun, Norman; Misron, Norhisam; Ishak, Mohamad Ridzwan (2005)
Power quality is very important to ensure a continuous and undisrupted operation of many on industrial processes. Nowadays, in the industrial environment, the industrial players in order to increase their output and maintain the quality of their products globally accept power electronic devices. However, a short disruption such as voltage sag may cause disorder on the sensitive devices, which may cause a substantial loss to a company. There are many different types of power conditioning solutions readily available in the market such as batteries, super capacitors, superconducting magnetic energy storage (SMES), fuel cells and flywheels. However, a correct understanding of load requirements is important in acquiring the suitable power solution device and besides that cost is also a factor. Each type of the solution has its own advantages and disadvantages on the efficiency, lifetime and maturity. Therefore from time to time, several solutions are invented to serve the needs and giving more choice to the customer. A flywheel energy storage system has some advantages especially on the cost, ruggedness an environmental friendliness. A flywheel system stores energy in the form of the kinetic energy. This kinetic energy varies linearly with the inertia of the flywheel and square of its angular velocity. In this paper, a mitigation method of voltage sag is proposed based on the idea of the static compensator (STATCOM). This system is developed a wider choice of solution to the voltage sag problem. A model of flywheel energy storage (FES) system and its simulation are presented. The flywheel is coupled with a DC machine, which is used to convert the energy of the flywheel, which is from electrical energy to kinetic energy and vice versa. A voltage source converter (VSC) is used as an interface between power line system and the flywheel as the storage system.